Imaging of Small Bowel Tumors and Mimics - Gupta, Pankaj; Lamichane, Saurav; Bhatia, Harsimran; Singhal, Manphool; Sharma, Vishal; Singh, Harjeet; Kumar, Rajender; Sandhu, Manavjit Singh (Journal of Gastrointestinal and Abdominal Radiology, 2023)
Small bowel tumors are rare with nonspecific and protean clinical presentation. Early diagnosis of small bowel tumors is desirable as they can be associated with significant morbidity. In malignant small bowel tumors, delayed diagnosis may result in dissemination and metastasis leading to poor clinical outcomes. Imaging evaluation of small bowel can be challenging due to unpredictable luminal distension, peristalsis, and motion. In addition, the lack of distinction between the intraluminal lesions and intraluminal contents can be difficult at times. Computed tomography (CT) and magnetic resonance (MR) enterography are the most common imaging techniques for the evaluation of small bowel tumors. While these techniques may not be able to detect small tumors, they provide comprehensive evaluation of lumen, wall, and extramural structures in tumors more than 2 cm. Acquaintance of imaging appearance of common benign and malignant small bowel tumors may allow improved detection during evaluation of CT and MR enterography studies. In this review, we discuss the imaging appearances, approach, and differential diagnosis of small bowel tumors on cross-sectional imaging studies.
Keywords: small bowel; tumors; CT; MRI